Літературне товариство імені Шевченка (1873—1892) в національній пам’яті українців - Соляр, І.Я. (Вісник НАН України, 2024)
Speech at the anniversary session of the general meeting of the National Academy of Sciences of Ukraine, dedicated to
the 150th anniversary of the Shevchenko Scientific Society, December 8, 2023.